Design revolution : 100 products that empower people. - Pilloton, Emily, ....- (New York : Metropolis, 2009)
Featuring more than 100 contemporary design products and systems--from high-tech waterless washing machines to Braille-based building blocks for blind children--this exceptionally smart, well-designed volume makes the case for design as a tool to solve some of the world's biggest social problems.